How administrations can influence foreign students in controlling multicultural issues? - Bijandi, Mohammad Sadegh; Hassan, Aminuddin (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
Global universities are becoming increasingly ethno culturally diverse. Two major social forces have contributed to this change: immigration and increasing enrolment of international students. They bring their values, language, culture and educational background to the campuses. To build an inclusive education, we have the ethical and educational responsibility to embrace such difference and diversity and to integrate it into all aspect of university life, including teaching, managing and learning. However, in our daily encounter with cultural diversity we still confront many challenges, which partially result from a lack of knowledge and readiness to approach diversity. The purpose of this literature research is to explore the ways in which factors are perceived and conceptualized by foreign students as members of the international academic community and how administrations academic and non-academic staffs can control them.